(3QSGdI aj Mb GdShGcs - (3GHf MeRI, eMeO Hf MeRI, cGf MjG (B1113 (3g`s ((3eMeO Hf GdMGL Ydj CafOjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg hSdGe Ydi YHGOg GdPj GUWai GYde Cf GdShGc ceG Gfg SfI ddQLGd SfI ddfSGA Od Ydjg GdSfI GdaYdjIs
(3BNQgG (B:s
(3dG jLhR ddeQCI Cf JSJGc hGdYdc bGFe ebGe GSJjGcf eeG dG jYhd Ydjg hdG jYQL dOjg deNGdaJg dUMjM GdOQGI hUQjM GdQhGjI hTPhPg ajeG jYe Hg GdHdhis
(3fSNI efbhdI Yf fSNI GdeDda eDQNI H SfI (B1103 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3 / 268s
(3agQS GdNOjhjI (B7 / 1 402s
(3agQS eNWhWGJ GdXGgQjIs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs